Strategi transformasi digital gramedia dalam industri majalah - Catharina Susy Triputranti; Benedictus A. Simangunson (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Abstract The growth of new media has forced the printed media industry to transform into online media, resulting in a number of consequences in the production process, which have to adapt with the needs of users in the digital era. This encouraged Gramedia of Magazine to carry out digital transformation strategy, to maintain sustainability of the media. This study utilizes the qualitative approach with the case study research method. Primary data collection in the research is done using interviews, observation, and document study. Results of the study show that a number of strategies must be carry out both in terms of the content production and resource, to support the transformation process and provide solutions for the sustainability of the media business. Keywords: Digital transformation; Media sustainability; New media;Media Strategy